Reducing Environmental Impact of Coal-Fired Power Plants by Building an Indoor Coal Storage: An Economic Analysis - JongRoul Woo; Jungwoo Shin; Seung-Hoon Yoo; Sung-Yoon Huh (Energies, 2023)
Coal-fired power plants have been identified as one of the major sources of air pollutants in the power sector. Most coal-fired power stations have large open-air coal stockpiles, which lead to a considerable amount of fugitive dust. The construction of an indoor coal storage is known to control coal dust; however, it requires significant upfront capital. Certain power utilities, including those in South Korea, are currently considering or are required to build indoor coal storages. This study analyzed the benefit and economic feasibility of indoor coal storages in coal-fired power stations. A contingent valuation method was used to elicit people’s willingness to pay for the construction of new indoor coal storages. The results showed that, on average, a South Korean household was willing to pay KRW 59,242 (USD 53.97) in a lump-sum payment toward the construction of indoor coal storages at six coal-fired power stations (total storage capacity of 5.47 million tons of coal, with a site area of 1.15 million m2). The resulting benefit–cost ratio of the project was calculated to be 0.52, which was not economically feasible. Thus, it is recommended that the South Korean government should focus on other cost-effective projects to improve air quality.